2011
DOI: 10.5897/ajpp10.226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial activity of Acalypha monostachya Cav. (Euphorbiales: Euphorbiaceae)

Abstract: Acalypha monostachya (Euphorbiaceae) is used by the inhabitants of San Rafael and ZapotitlanSalinas, Puebla, Mexico, to alleviate illnesses of bacterial and fungal origin. We analyzed the antimicrobial activity of A. monostachya and some of its chemical features. The extracts were obtained by percolation. The antibacterial and antifungal activities were examined through the disc-diffusion method. The general toxicity was carried out by using Artemia salina. The quenching of free radicals by extracts was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
7
5
0
Order By: Relevance
“…55,[58][59][60][61][62][63][64][65] Another study demonstrated that antifungal potency may be due to the abundance of linoleic and α-linolenic acids in the major fraction of fatty acids methyl esters. [66][67][68] In our previous study we confirmed the significant relation between the severity of AD and the occurrence of food hypersensitivity reactions to sea fishes; the reactions to sea fishes are recorded in 8% of patients suffering from mild form of AD, in 8% of patients suffering from moderate form of AD and in 28% of patients suffering from severe form of AD. 29,30 Another reason for the significant direct relation between the sensitisation to fungi and the occurrence of food hypersensitivity reactions to nuts and fishes may be the fact that positive SPT reactions to fungi are mostly observed in patients with multiple sensitivity to various allergens.…”
Section: Discussionsupporting
confidence: 67%
“…55,[58][59][60][61][62][63][64][65] Another study demonstrated that antifungal potency may be due to the abundance of linoleic and α-linolenic acids in the major fraction of fatty acids methyl esters. [66][67][68] In our previous study we confirmed the significant relation between the severity of AD and the occurrence of food hypersensitivity reactions to sea fishes; the reactions to sea fishes are recorded in 8% of patients suffering from mild form of AD, in 8% of patients suffering from moderate form of AD and in 28% of patients suffering from severe form of AD. 29,30 Another reason for the significant direct relation between the sensitisation to fungi and the occurrence of food hypersensitivity reactions to nuts and fishes may be the fact that positive SPT reactions to fungi are mostly observed in patients with multiple sensitivity to various allergens.…”
Section: Discussionsupporting
confidence: 67%
“…The findings of the present study explain why the plant extracts are used in traditional folk medicine and confirm the activity of A. manniana as a broad spectrum antimicrobial agent since it inhibited the growth of Gram-positive ( S. aureus , E. faecalis ) and gram negative bacteria ( E. coli , P. aeruginosa , K. pneumoniae, P. mirabilis , S. paratyphi A , S. paratyphi B , S. flexneri) as well as some fungi ( T. mentagrophytes , T. terrestre , T. equinum , M. gypseum ). Similar findings had been reported for other species by Canales et al (2011) and Haruna et al (2013). The antimicrobial activities of A. manniana (MIC = 0.25 - 2.04 mg/mL) can also be considered very important compared with those of Haruna et al (2013) who reported the antimicrobial activities of the leaves of A. wilkesiana methanolic extract and its four derivative fractions (MIC = 25–100 mg/mL) on human pathogenic bacteria namely S. aureus , S. pyogenes , E. faecalis , P. aeruginosa , P. vulgaris , E. coli, Aspergillus niger , A. flavus , A. carbonerium , T. mentagrophytes and Candida albicans .…”
Section: Resultssupporting
confidence: 92%
“…These compounds varied within the fractions. In agreement with our results, the phytochemical screening of the leaf extracts of Acalypha hispida, A. marginata, A. racemosa, A. monostachya, A. alnifolia , A. wilkesiana and A. indica revealed the presence of phenolics, tannins, steroids, flavonoids, glycosides, saponins and anthraquinones that varied within the plant species (Iniaghe et al 2009; Gotep et al 2010; Canales et al 2011; Evanjelene & Natarajan 2012; Mohan et al 2012). …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations